Peningkatan Kesadaran Pemberian ASI Eksklusif Di Desa Tingkeum Kecamatan Nisam Dalam Upaya Pencegahan Stunting Kota Lhokseumawe - Andyna, Cut; Ritonga, Nursakinah; Khairisma, Khairisma; Husna, Asmaul; Nazaruddin, M.; Hafni, Nur; Alawi, Muh. Fahrudin (Jurnal Solusi Masyarakat (JSM), 2024)
This service is carried out as a form of joint responsibility of all parties, in this case academics to play an active role in the Prevention of stunting. This is a support for government programs to significantly reduce stunting cases in Indonesia. One effective effort that can be done is to support exclusive breastfeeding (ASI) in the first 6 months until the age of 2 years. The great benefits of breastfeeding for children's growth and development become one of the government's foundations to make exclusive breastfeeding one of the joint movements implemented in various ministry programs. Failure to breastfeed can cause a shortage of brain cells in children which will then affect the inhibition of the development of infant intelligence at a later stage. This service activity was carried out in several stages; (1) Coordination of preparation for the implementation of activities with Posyandu cadres in Tingkuem Village, nisam District, (2) Implementation of educational activities in the form of socialization on the importance of exclusive breastfeeding with several groups of pregnant and lactating women. This service is expected to increase the knowledge of mothers consisting of groups of pregnant women, nursing mothers and parents regarding exclusive breastfeeding and balanced nutrition for pregnant and lactating women.